CAR-M therapy in the era of tumor immunotherapy: current research progress and engineering strategies - Yang, Yi-Min; Ding, Yu-Fan; Hu, Yi-Yang; Fan, Fan; Zhao, Jun-Long (Frontiers in Immunology, 2026)
Chimeric antigen receptor (CAR) cellular immunotherapy has emerged as a revolutionary modality in cancer treatment. CAR-T cell therapy has demonstrated remarkable efficacy against hematological malignancies; however, its application in solid tumors is significantly constrained by inadequate tumor infiltration, a profoundly immunosuppressive tumor microenvironment (TME), and pervasive antigen heterogeneity. Conversely, macrophages — innate immune cells inherently poised within tissues — exhibit superior tumor-tropic migration, potent phagocytic capability, and a unique capacity to remodel the TME, establishing CAR-engineered macrophages (CAR-M) as a highly promising next-generation therapeutic platform. Despite this considerable promise, the clinical translation of CAR-M faces several critical bottlenecks, including heterogeneity in cell sources, challenges in manufacturing standardization, risks of on-target/off-tumor toxicity, and the dynamic, immunosuppressive nature of the TME. This review offers a systematic and in-depth analysis of the current research landscape and engineering advances in CAR-M therapy. It comprehensively details the molecular evolution of CAR-M designs, spanning from early constructs to sophisticated logic-gated circuits and innovative in vivo generation strategies utilizing lipid nanoparticles (LNPs). We critically evaluate the applicability and limitations of various cellular sources, such as peripheral blood mononuclear cells (PBMCs), induced pluripotent stem cells (iPSCs), and the THP-1 cell line. Furthermore, the review elucidates the multimodal antitumor mechanisms of CAR-M, including the direct “phagocytosis-presentation-activation” cascade, synergistic potential with immune checkpoint blockade, and deep reprogramming of the immunosuppressive TME. By synthesizing the latest preclinical and emerging clinical evidence, this article underscores the distinctive advantages and delineates a translational roadmap for CAR-M development. It is intended to serve as an authoritative reference for the field, providing strategic insights into intelligent receptor design, precision biomanufacturing, and rational combination therapies aimed at overcoming the enduring barriers in solid tumor immunotherapy.